The library and its future challenges: Do we need the same strategy? - Juárez-Urquijo, Fernando (Anuario ThinkEPI, 2018)
The term "˜one-person library´ is used within the English-speaking world in order to refer to libraries managed by just one person; "˜solo librarian´ refers to the professional in charge of those libraries. Although in Spain official statistics do not reflect this, the situation of most of the Spanish public libraries is similar to these "˜one-person libraries´; precarious working conditions, lack of resources, and professional loneliness are typical. If we take into account a working environment that is far from easy, we can see that everyday work does not provide enough time to think about the relevance of the services that the library offers, instead it is almost compulsory to replicate, without much thought, what other public libraries are doing, usually with more resources and different realities. To delegate the construction or essence of the library to others can be counterproductive to successfully face the challenge of adapting to a new digital environment. To adopt someone else´s strategies without taking into account its own peculiarities can make us fail and take us far from the essence of a suitable library for our community.
Keywords: Library mission; Library values; Core values; Librariness; Future of libraries.